Análisis Descriptivo Comparativo Entre Proyectos Integradores De Saberes En Carreras A fines A Comunicación - Salguero Rosero, José Rafael (2017)
The article presents a documentary, descriptive and comparative analysis between the integration project methodology of the of knowledge (WEE), executed in Graphical Design career of Chimborazo's National University (UNACH) and Social Communication career mention in Advertising and Design, of the International University of the Ecuador (UIDE) in Guayaquil. The aim is to base theoretical, technical and methodological parameters that guarantee right results in subsequentof integration projects, from his conception up to the evaluation. It presents theoretical and structural contributions that they can be applied in any discipline field or career. The principal conclusion to the one that comes near is: the WEE is a strategic didactic method to promote the autonomy in the learning, the experimentation and the multidisciplinary work. It provides means and resources for a constant evaluation, demonstrating, both the individual growth of the pupil and the progress in equipment. It provides means and resources for a constant evaluation, demonstrating, both the individual growth of the pupil and the progress in equipment. The socialization of the results will help to strengthen the didactic competitions of the teachers in the higher education, applying the cooperative learning.